2021
DOI: 10.1002/tpg2.20080
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction enables rapid selection of high‐performing genets in an intermediate wheatgrass breeding program

Abstract: In an era of constrained and depleted natural resources, perennial grains could provide sustainable food production along with beneficial ecosystem services like reduced erosion and increased atmospheric carbon capture. Intermediate wheatgrass (IWG) [Thinopyrum intermedium (Host) Barkworth & D. R. Dewey subsp. intermedium] has been undergoing continuous breeding for domestication to develop a perennial grain crop since the 1980s. As a perennial, IWG has required 2-5 yr per selection generation, but starting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…Each year phenotypic traits were measured to evaluate genet performance, with a total 34 unique traits (Crain et al 2021a). Within the breeding program the most important traits which are key selection targets include shattering, percent free-threshing seed, seed mass, and spike yield.…”
Section: Phenotypic Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Each year phenotypic traits were measured to evaluate genet performance, with a total 34 unique traits (Crain et al 2021a). Within the breeding program the most important traits which are key selection targets include shattering, percent free-threshing seed, seed mass, and spike yield.…”
Section: Phenotypic Assessmentmentioning
confidence: 99%
“…Interestingly, we identified that 2.3% (548 markers) had diverged between TLI-cycle 6 and 9, yet only four of the 217 MTAs showed high or very high FST. Since genomic selection has been exclusively used for the last four breeding cycles (Crain et al 2021a), we evaluated the genome-wide estimated marker effects for yield traits. Of the 72 highly diverged markers, 60% and 56% (43 and 40 markers respectively) had coefficients with higher spike yield and seed mass and the mean of all these markers indicated selection was in the favorable direction.…”
Section: Gwas In a Breeding Populationmentioning
confidence: 99%
See 3 more Smart Citations